Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Trouble dans le genre : pour un féminisme de la subversion - Butler, Judith (La Découverte, 2005)
Dans cet ouvrage majeur publié en 1990 aux États-Unis, la philosophe Judith Butler invite à penser le trouble qui perturbe le genre pour définir une politique féministe sans le fondement d’une identité stable. Ce livre désormais classique est au principe de la théorie et de la politique queer : non pas solidifier la communauté d’une contre-culture, mais bousculer l’hétérosexualité obligatoire en la dénaturalisant. Il ne s’agit pas d’inversion, mais de subversion. Judith Butler localise les failles qui témoignent, à la marge, du dérèglement plus général de ce régime de pouvoir. En même temps, elle questionne les injonctions normatives qui constituent les sujets sexuels. Jamais nous ne parvenons à nous conformer tout à fait aux normes : entre genre et sexualité, il y a toujours du jeu. Le pouvoir ne se contente pas de réprimer ; il ouvre en retour, dans ce jeu performatif, la possibilité d’inventer de nouvelles formations du sujet. La philosophe relit Foucault, Freud, Lacan et Lévi-Strauss, mais aussi Beauvoir, Irigaray, Kristeva et Wittig, afin de penser, avec et contre eux, sexe, genre et sexualité – nos désirs et nos plaisirs. Pour jeter le trouble dans la pensée, Judith Butler donne à voir le trouble qui est déjà dans nos vies
Première publication: 1990
Keywords: amériques; approches et analyses; com5170; cours; cycles supérieurs; discipline; fem1000; fem3200; fem7000; genre; har4600; identités LGBTQIA2+; incontournable; lit3220; lit4700; philosophie; premier cycle; queer; régions géographiques; sciences humaines; sexe; sexualité; soc2014; thématiques; états-unis

L'évidence de l'égalité des sexes : une philosophie oubliée du XVIIe siècle - Dorlin, Elsa (L'Harmattan, 2000)
Au XVIIe siècle, quatre philosophes, à quelques décennies d'intervalle, formulent en des styles très différents la thèse selon laquelle l'égalité entre les hommes et les femmes est une évidence, une vérité indiscutable. Marie de Gournay, Anna Maria Van Schurman, François Poullain de la Barre et Gabrielle Suchon, estiment que si les interdictions et les discriminations frappant les femmes perdurent, c'est que la querelle entre les défenseurs et les pourfendeurs du " Beau Sexe " est biaisée : les présupposés de la différence sexuelle rendent la question de l'égalité ou de l'inégalité des sexes indécidable.
Donné en lecture cours FEM1000: p.11-14 et 17-32
Keywords: 1600-1699; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; histoire des femmes*; histoire et politique; incontournable; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme